Implementasi Sistem One Piece Flow untuk Mengurangi Lead Time Produksi pada Industri Garmen - Nancy Oktyajati; Sri Mayasari; Sri Purwati (Program Studi Teknik Industri Universitas Setia Budi, 2023)
Garment industry often faces many problems such as low productivity, long lead time production, high product rework and rejection, improper line balancing, and inflexible style running changeover. The aim of this research is to implement one of the lean concept tools namely one piece flow. This study focuses on Sewing Department of Man Shirt Unit in a Garment Company in Central Java, Indonesia. The study of this paper includes the description of garment manufacturing process flow and comparison between the batch production system and one-piece flow system. The performance criteria used in this study is the total processing time, the basic pitch time, the production targets and the throughput time. The time study is used as the measurement method to determine the cycle time and throughput. From the analysis, one piece flow system performs better in term of total processing time, the basic pitch time and the throughput time and the target achievement than batch production system. The total processing time and pitch time reduced by 6.42 % and 0.385% respectively. The daily target quantity increased by 8.609% and tThe troughput time of 1 piece of good garment in assembly line reduced from 3.35 hour to 0.915 hour.